(untitled) (KONFERENSIYA, 2025)
The article examines the sociolinguistic and semantic features of the functional-semantic field of “ugliness” in English and Uzbek. The study analyzes the evaluative, emotional, and culturally marked components of lexical units expressing negative aesthetic and moral qualities. Special attention is paid to anthropocentric motivation, metaphorical extensions, and sociocultural connotations in both languages. The comparative analysis demonstrates that the linguistic conceptualization of “ugliness” reflects national value systems, cultural norms, and social judgments embedded in English and Uzbek linguistic worldviews